The Transition to Mental Health Services From the Perspectives of Neurodivergent Young People, Caregivers and Mental Health Professionals: A Constructivist Grounded Theory Approach - Kim Tang; Robert Wells; Craig Thompson; Elizabeth Hill; Elizabeth Pellicano; Bronwyn Myers (Journal of Autism and Developmental Disorders, 2026)
Abstract Purpose The prevalence of mental health conditions is increasing globally, with mental health difficulties the leading cause of disability for young people aged 12 to 25 years. Neurodivergent young people are up to three times more likely to develop a co-occurring mental health condition, requiring formal support from childhood to adulthood. They also experience delayed access to adult mental health care once they have been discharged from child mental health services. This study aimed to investigate what could support neurodivergent young people to transition from child to adult mental health services. Methods This qualitative research made use of a constructivist grounded theory approach. Three participant groups were recruited for this study, including 12 neurodivergent young people, 6 caregivers, and 5 healthcare professionals. Semi-structured interviews were used as the primary source of data with a follow-up workshop. Results We identified three themes. Across all three groups, participants emphasised that the care delivered by healthcare professionals is constrained by the structures of the mental health system, thereby limiting the level of neuro-affirming care they can implement. These limitations made the informal support that parents and caregivers provided more critical in assisting them with the service transition. Conclusion This study provided new insight into what could support neurodivergent young people to transition from child to adult mental health services. The findings in this study highlight the need to develop both provider- and system-level capacity to better support this service transition, to reduce the burden on neurodivergent young people and their informal supports.